Implementasi Pengelolaan Keuangan Badan Usaha Milik Desa Dengan Peraturan Pemerintah No. 11 Tahun 2021 (Studi Kasus BUMDes Anugrah Mulya Di Kabupaten Madiun) - Eka Febiana Nurdiyawati; Nur Sayidatul Munti'ah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
BUMDes Anugrah Mulya, which is used as a research site, is located in Candimulyo Village, Dolopo District, Madiun Regency, East Java. The purpose of this research is to find out how current financial management at BUMDes Anugrah Mulya with Government Regulation No. 11 of 2021. Therefore, the role of the manager is also very important in implementing appropriate financial management. The descriptive qualitative method was chosen by researchers in this research through a process of observation, interviews, and documentation (data triangulation). The form of government business that is realized to increase the village's original income and support the development of the village is known as Village-Owned Enterprises (BUMDes). Village governments establish BUMDes to help improve village welfare. One of the BUMDes in Madiun Regency provides several services for the community, especially in the fulfillment of basic materials and services. This can certainly help and have a positive impact on the surrounding community. The results shown in this research show that the financial management in BUMDes Anugrah Mulya is not appropriate because the reports reported on accountability are incomplete. This is constrained by Human Resources who are less competent in managing financial reports with the specified standards. This research is expected to be used as advice and evaluation so that financial management is given more attention.